IL-27 mediates the response to IFN beta therapy in multiple sclerosis patients by inhibiting Th17 cells - Fletcher, Jean; Basdeo, Sharee; Mills, Kingston (My University, 2011)
Interferon (IFN)-? is a commonly used therapy for relapsing remitting multiple sclerosis (RRMS). However its protective mechanism is still unclear and the failure of many patients to respond has not been explained. We have found that IFN-? suppressed IL-23 and IL-1? production and increased IL-10 production by human dendritic cells (DC) activated with the TLR2 and dectin-1 agonist zymosan. Furthermore, IFN-? impaired the ability of DC to promote IL-17 production by CD4+ T cells, but did not affect IFN-? production. IFN-? induced IL-27 expression by DC, and neutralisation of IL-27 abrogated the suppressive effects of IFN-? on zymosan-induced IL-1 and IL-23 production and the generation of Th17 cells in vitro. Complementary in vivo studies in a mouse model showed that treatment with IFN-? enhanced expression of IL-27, and reduced IL-17 in the CNS and periphery and attenuated the clinical signs of experimental autoimmune encephalomyelitis (EAE). In addition, the significant suppressive effect of IFN-? on the ability of DC to promote Th17 cells was lost in cells from IL-27 receptor deficient mice. Finally, we showed that PBMC from non-responder RRMS patients produced significantly less IL-27 in response to IFN-? than patients who responded to IFN-? therapy. Our findings suggest that IFN-? mediates its therapeutic effects in MS at least in part via the induction of IL-27, and that IL-27 may represent an alternative therapy for MS patients that do not respond to IFN-?.
PUBLISHED
Keywords: Immunology; multiple sclerosis; Interferon (IFN)-?; Th17; IL-27; dendritic cell; Immunology, Inflammation & Infection; Neuroscience